Developing a logic model for youth mental health: participatory research with a refugee community in Beirut - Afifi, Rema A (Oxford University Press, 2011)
Although logic models are now touted as an important component of health promotion planning, implementation and evaluation, there are few published manuscripts that describe the process of logic model development, and fewer which do so with community involvement, despite the increasing emphasis on participatory research. This paper describes a process leading to the development of a logic model for a youth mental health promotion intervention using a participatory approach in a Palestinian refugee camp in Beirut, Lebanon. First, a needs assessment, including quantitative and qualitative data collection was carried out with children, parents and teachers. The second phase was identification of a priority health issue and analysis of determinants. The final phase in the construction of the logic model involved development of an intervention. The process was iterative and resulted in a more grounded depiction of the pathways of influence informed by evidence. Constructing a logic model with community input ensured that the intervention was more relevant to community needs, feasible for implementation and more likely to be sustainable.